Optimizing of pharmaceutical active compounds biodegradability in secondary effluents by β-lactamase from Bacillus subtilis using central composite design - Al-Gheethi, Adel; Noman, Efaq; Radin Mohamed, Radin Maya Saphira; Ismail, Norli; Abdullah, Abd Halid; Mohd Kassim, Amir Hashim (Elsevier, 2019)
Biodegradation of pharmaceuticals active compounds (PACs) in secondary effluents by using B. subtilis 2012WTNC as a function of β-lactamase was optimized using response surface methodology (RSM) designed by central composite design (CCD). Four factors including initial concentration of bacteria (1–6 log10 CFU mL−1), incubation period (1–14 days), incubation temperature (20–40 °C) and initial concentration of PACs (1–5mg L−1) were investigated. The optimal operating factors for biodegradation process determined using response surface methodology (RSM) was recorded with 5.57 log10 CFU mL−1 of B. subtilis, for 10.38 days, at 36.62 °C and with 4.14 mg L−1 of (cephalexin/amoxicillin) with R2 coefficient of 0.99. The biodegradation was 83.81 and 93.94% respectively. The relationship among the independent variables was significant (p < 0.05) with 95% of confidence level at the best operating parameters. The bioassay for PACs after the degradation